Evaluation Of Criticism About Narrators - Avcı, Seyit (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2011)
By the time some different schools and groups of societies have criticized the narrators who collected the hadites of the prophet recording in books and serving Muslim ummah by protecting them from getting lost. Within these critics are some that claim narrators related contradicting make up, traditions, contended with verbal knowledge, become irregular with their prayers, neolected the Holy Qur'an, allowed to rumour by nearing their gossiping, being proud of their knowledge running after wordly benefits and had failed to understand the sense of hadith. However these critics are not against all narrators but meaning to certain groups to criticize. Thus putting all narrators under suspicion is not consistent and do not agree with the science of knowledge. All activities of narrators mean to make Muslims more religious and follow hadithes more. The narrators whom history with-nessed that the fulfilled their duties peewishly in collecting the hadithes scattered to different regions of Islamic geography having done their best in refining them then related those as hadithes. No one is entitled to blind these works. Muslims' learning all details about the Prophet, for sure, owe much the understanding of Islam depending on hadith and narrators have the greatest role in this service.
Keywords: Hadith; Traditionist; Criticism; Rumor; Science